(untitled) (Fiep Bulletin - online, 2014)
It was a fieldwork aiming to evaluate rates of quality of life in patients that underwent chemotherapy. The research was conducted in UOPECCAN – West of Paraná State Union of Studies and Fight against Cancer, in Cascavel city. The instrument used for data collection was the questionnaire EORTIC QCQ-C30 version 3.0, answered by 70 ambulatory patients under chemotherapeutic treatment, from different phases of the malignant neoplasm disease, in different cycles of chemotherapeutic drugs to be assessed by the viewpoint of their subjunctive perception of quality of life during the ambulatory stay for treatment. The individuals were evaluated in the physical health, physiological and psychosocial fields. The results showing quality of life implications are highlighted. In relation to physiologic changes it was found that 42,85% of the youngsters had limitations for leasure activities; in terms of pain, the youngsters had a representation of 35,71%, while in the elders it was 23,21%; in sleep disturbance matter 25% of the elderly patients showed difficulties. It is pointed that psychosocial changes in both age groups showed relevant values in relation to nervous tension, what indicates that this information presents interference in quality of life, considering that in the 41-80 years old group the patients had a negative compromising in the significant statistically family context. Through the data obtained it’s seen that altogether there is high incidence of the collateral effects that the chemotherapeutic drugs produce over the patient’s health who undergo treatment. However, the set of results shown permitted to visualize that in the chemotherapeutic treatment period from the studied sample, in a general view, there wasn’t negative impact in the individuals’ health capable of decaying the quality of life.